Prospecção de nanocápsulas para carreamento de curcumina em Caenorhabditis elegans: estratégia para manejo do processo inflamatório associado à Covid-19 - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The COVID-19 pandemic has resulted in an unprecedented increase in illness, death, economic disruption and social unrest around the world. There were no strategic plans ready to apply to a coronavirus pandemic. Although many drugs are approved, their effectiveness is often limited because these drugs are not specific for this new virus. In this context, natural compounds such as curcumin have shown effectiveness in the progression of diseases due of their therapeutic potential. Despite the numerous beneficial effects of curcumin, it has low solubility and bioavailability, instability in body fluids and rapid metabolism. One of the promising strategies to optimize the effectiveness of many therapeutic agents are nanoparticulate drug delivery systems. However, the security of these systems is an aspect to be understood, especially in vivo systems. In this sense, we first investigated the safety of four different nanoparticulate systems using Caenorhabditis elegans (C. elegans) as an alternative model. The objective of this study was to evaluate toxicological outcomes, such survival, reproduction, development and oxidative damage in C. elegans acutely (30 minutes) or chronically (48 h) exposed to nanocapsules (NC) composed of different components: polysorbate 80 (P80), polyethylene glycol (PEG), Eudragit® (EUD) and chitosan (CS). Our initial results indicated that these formulations present a degree of toxicity in this organism; we detected an increase in the mortality of worms exposed acutely to nanocapsules composed of PEG and CS at the highest concentrations and an increase in mortality of worms chronically exposed to P80, PEG and CS. The expression levels of antioxidant superoxide dismutase were determined and our results showed an increased expression only following NCP80 treatment at the highest concentration. Notably, our results demonstrated that nanocapsules with the EUD component were safer for C. elegans and thus, used to develop curcumin-loaded nanocapsules (NCCM) and to evaluate their toxicological effects, through the parameters of survival, reproduction and development, as well as their protective effects of lipopolysaccharide (LPS- induced inflammatory injury in C. elegans. NCCM showed no toxicity to the worms and protected them from LPS-induced injury, rescuing behavioral phenotypes, such as reversal and omega turn movements, decreasing apoptotic effects. These nanoformulations have shown to be safe and promising, improving the bioavailability of curcumin and becoming promising adjuvants in the treatment of inflammatory diseases such as the cytokine storm in COVID-19.
Prospection of nanocapsules for carrying curcumin in Caenorhabditis elegans: a strategy for managing the inflammatory process associated with Covid-19
Keywords: Nanotoxicidade; Polímeros; COVID-19; Drug repositioning; Curcumin; Curcumina; Nanotoxicity; Polymers; Caenorhabditis elegans; SARS-CoV-2; CNPQ::CIENCIAS BIOLOGICAS